Program bimbingan wawasan dan kesiapan karier di pondok pesantren salafiyah tingkat SMP - Bahrin, Sitirahma (TAWAZUN: Jurnal Pendidikan Islam, 2025)
The career problem often faced by junior high school students in salafiyah pesantren is the lack of insight and ideas about the steps to be taken in the future. This study aims to develop a structured, systematic, and sustainable career insight and readiness guidance program for junior high school students. The method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The needs analysis showed that 74% of students experienced career problems and 100% of boarding school managers stated the need for a career guidance program. The program was developed by adapting the Super measurement tool and referring to Permendikbud No. 111 of 2014, with materials such as recognizing self-potential, strengths and weaknesses, and readiness for success. Expert validation results showed a high level of feasibility: experts in Islamic Religious Education (84.6%), guidance and counseling (77.7%), and Indonesian language (92.5%). Practitioner tests in five pesantren obtained percentages between 81% and 95%, with the average in the “feasible” category. Thus, this guidance program is declared feasible to use as a supporting instrument for the career readiness of junior high school students in salafiyah pesantren, and contributes to the development of career guidance services based on Islamic education. Abstrak Permasalahan karier yang sering dihadapi siswa sekolah menengah pertama di pesantren salafiyah adalah kurangnya wawasan dan gagasan mengenai langkah yang harus ditempuh di masa depan. Penelitian ini bertujuan mengembangkan program bimbingan wawasan dan kesiapan karier yang terstruktur, sistematis, dan berkelanjutan untuk santri usia sekolah menengah pertama. Metode yang digunakan adalah Research and Development (R&D) dengan model ADDIE (Analysis, Design, Development, Implementation, Evaluation). Analisis kebutuhan menunjukkan bahwa 74% siswa mengalami permasalahan karier dan 100% pengelola pondok menyatakan perlunya program bimbingan karier. Program disusun dengan mengadaptasi alat ukur Super dan mengacu pada Permendikbud No. 111 Tahun 2014, dengan materi seperti mengenal potensi diri, kelebihan dan kekurangan, serta kesiapan menuju kesuksesan. Hasil validasi ahli menunjukkan tingkat kelayakan yang tinggi: ahli Pendidikan Agama Islam (84,6%), bimbingan dan konseling (77,7%), dan bahasa Indonesia (92,5%). Uji praktisi di lima pesantren memperoleh persentase antara 81% hingga 95%, dengan rata-rata dalam kategori “layak”. Dengan demikian, program bimbingan ini dinyatakan layak digunakan sebagai instrumen pendukung kesiapan karier santri SMP di pesantren salafiyah, serta berkontribusi pada pengembangan layanan bimbingan karier berbasis pendidikan Islam.